A night at the Gardens class, gender, and respectability in 1930s Toronto - Field, Russell (University of Toronto Press, 2023)
"When Toronto's Maple Leaf Gardens opened in 1931, manager Conn Smythe envisioned an arena that would project an aura of middle-class respectability. In A Night at the Gardens, Russell Field shares how this new arena anticipated spectators by examining varying spectator behaviours, who the spectators were, and what the experience of spectating was like. Drawing on archival records, the book explores the neighbourhood in which Maple Leaf Gardens was situated, the design of the arena's interior spaces, and the ways in which it was operated in order to appeal to respectable spectators at a particular intersection of class and gender. Examining a ticket ledger compiled by arena staff for the 1933-34 National Hockey League season, the book reveals that the average subscriber purchased more than two tickets, suggesting that attending hockey games was a social experience. It also shows that while ticket subscribers were overwhelmingly middle-class men, women were also present. Oral history interviews with twenty-one former spectators at the Maple Leaf Gardens detail the experience of watching the spectacle that unfolded on the ice during each hockey game. A Night at the Gardens tells the fascinating story of how one prominent public building became such an important part of Toronto society."--